(untitled) (Journal of Pakistan Orthopaedic Association, 2015)
Objective: To evaluated the effect of the steroid injection in the management of pain with plantar fasciitis patients. Methods: This descriptive case series study enrolled 56 patients with symptomatic plantar fasciitis to treatment with SI, aged ?18 years were selected from orthotics departments of HOPE Center, Pakistan from Mar 2013 to Dec 2013. All patients were assessed for patient history and pain relief at 1 and 6 months for pain relief after the initiation of steroid injection treatment. Results: Out of 56 patients; 38(67.85%) were male & 18(32.14%) were female. The mean age and BMI of the patients was 37.76±13.35 years and 28.32±1.52. Only 45/56(83.5%) got relieved after using treatment at one and six months follow–up, four patients became lost to follow up and five patients changed their initial treatment during the 6 month follow-up because did not experience relief. Results showed significant improvement in pain at four weeks was 42/51(82.35%) as compare to six month was 3/5(60.0%) , associated with lower compliance as ISE (2%), ISI (1%), and PFR (2.8%). However, pain relief was showed significant difference after treatment at 4 weeks as (4.05±1.18) and insignificant at six month follow-up (3.94 ± 2.40). Conclusion: Steroid infection is safe and effective method and provides short-term pain relief for patients with plantar fasciitis but for long term pain relief was insignificant and improvement was not sustained. Key Words: Plantar fasciitis, Steroid Injection, Injection site infection.